PERGESERAN NILAI-NILAI BUDAYA PADA SUKU BONAI SEBAGAI CIVIC CULTURE DI KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU PROVINSI RIAU - Prayogi, Ryan; Danial, Endang (Faculty of Humanities, Diponegoro University, 2016)
This research was grounded by social problems, which is a shift of cultural values and global transformation with positive and negative values including waning identity tribe Bonai, such as change the culture in the form of traditional values in traditional ceremonies as a result of changes in the environment their lives, both the natural environment and the physical and social environment such as the loss of a sense of kinship, courtesy, honesty, and mutual cooperation. The findings in this study revealed that 1) the tribe Bonai a principle of life that becomes a guideline and regulations that must be adhered to by the tribal people Bonai hereditary implemented include: Birth, Circumcision Rosul, Employment, Education, Marriage Married, Leadership System Society, Death. 2) The shifting cultural mores which are currently experiencing a shift towards cultural values that include a shift in values Nativity, Circumcision Rosul, Marriage, and Ritual Dewo. 3) Preservation made to the successor or the younger generation by providing knowledge about the culture, following the race on culture or festival and explain the meanings contained in each ceremony they have done, executing each set of tribal Bonai traditions, which are birth, circumcision messenger, dewo mating and rituals for marriage. 4) Development of indigenous culture as do general should be imparted to young people from birth to adulthood through education and infomal also goes by way of natural or natural and spontaneous. In particular the development of the cultural values taught to elementary school through high school